Health Belief Model Application in Bone Fracture Treatment-Seeking Behavior: Preferences for Traditional Bone-Setting Treatment versus Orthopedic Surgery - Miswanto, Miswanto; Bhisma Murti; Setyo Sri Rahardjo; Sulaeman, Endang Sutisna; Sri Mulyani (Indonesian Journal of Medicine, 2025)
Background: Bone fractures are a significant public health issue, with 178 million new cases globally in 2019 and a prevalence of 5.5% in Indonesia. The Indonesian community tends to choose traditional treatment such as herbal medicine or surgical treatment for fractures, influenced by sociodemographic factors, culture, and individual perceptions. This study aims to analyze the Health Belief Model (HBM) factors that affect the choice of bonr fracture treatment services in the community. Subjects and Method: This cross-sectional study was conducted in Surakarta during April–May 2025, involving 200 participants, comprising 100 users of traditional bone-setting treatment and 100 users of orthopedic care. Data were collected using an online questionnaire covering demographic characteristics and HBM constructs. The data were analyzed using univariate methods, bivariate analysis with simple logistic regression, and multivariate analysis employing path analysis. Results: The decision to choose type bone fracture treatment care was directly influenced by perceived susceptibility (b = -2.30; 95% CI: -3.09 to -1.50; p < 0.00), benefits (b = 1.80; 95% CI: 0.89 to 2.72; p < 0.00), self-efficacy (b = 1.36; 95% CI: 0.51 to 2.22; p < 0.00), and action cues (b = 3.80; 95% CI: 1.70 to 5.90; p < 0.00), while the perception of barriers indirectly lowers self-efficacy (b = -0.65; 95% CI: -1.29 to -0.02; p < 0.04). Conclusion: The HBM constructs, especially perceived vulnerability, benefits, self-efficacy, and action cues, significantly influence the choice of treatment for fractures. Educational interventions are recommended to enhance the perception of the benefits of medical services and strengthen the self-efficacy of the community.